Psychologists' understanding of the factors influencing successful treatment in a secure forensic environment. Issue 3 (13th August 2018) - Gale, Jessica; Clarbour, Jane; Rayner, Kelly
Abstract : Purpose: Literature suggests that mentally disordered offenders are considerably more difficult to treat and slower to respond to psychological treatment. Less is known about the particular factors that can contribute to this resistance. A more comprehensive understanding of the factors that treating psychologists feel can promote or inhibit progression through rehabilitative treatment may increase the likelihood of positive clinical outcomes. This paper aims to discuss these issues. Design/methodology/approach: Four practising psychologists employed within a male medium- and low-secure forensic unit in the North East of England took part in a semi-structured interview. Their views, opinions and experiences regarding patient progression through treatment pathways were recorded, transcribed and analysed. Findings: This thematic analysis identified that numerous patient-specific parameters influenced perceived progression, and environmental and external factors had a significant impact on the patients' expressed attitude towards treatment. Practical implications: Alongside issues of motivation and engagement, participants identified external factors that influence perceived treatment success with their forensic patients. Originality/value: Additional research is needed to identify the factors that are the most influential in promoting or inhibiting perceived and actual progress. This will hopefully optimise treatment engagement and the motivation to change problematic behaviours in mentally disordered offenders.